The application of airborne geophysics data for rapid regional geological mapping in Northwestern Angola - Zhang, Hongrui; Jia, Pengfei; Zhang, Xu; Wang, Zhigang (Penerbit Universiti Kebangsaan Malaysia, 2017)
Airborne prospecting (spectrum, magnetics) measurement is an effectively auxiliary approach for geological mapping. It effectively measures the magnetic field characteristics and the surface contents of the most common three radioactive elements (K,eU and eTh) of nature in the research area. Given the significant diversities of magnetic characteristics and the radioelements’ contents of different lithological units, these can be applied into the mapping of shallow overburden area. Ternary MAP is a compound imaging technology, providing the radioelements contents a simultaneous display on the same pixel. Based on colour differences, this technology can identify different lithologies and clithofacial changes in the same lithological unit effectively in a certain area. With aeromagnetic data conversion and integrated spectrum images, a good effectiveness of 1:250,000 lithological-structural mapping has been achieved in the research area of Northwestern Angola.